Admission to Educational Organizations in Case of Refusal to Vaccinate - Polina G. Gabay; Sophia A. Dronova ("Paediatrician" Publishers LLC, 2020)
The aspects of the refusal to perform preventive vaccination and its outcomes in the frame of admission to educational organizations, as well as aspects of separation of vaccinated children from non-vaccinated ones are considered in this article according to the current legal regulation for this topic and to the litigation practice materials. Recommendations on Russian legislation improvement in the area of interest have been developed. The possibility of children (without performed tuberculin sensitivity test) admission to educational organizations is analyzed. The admissibility of the requirements for medical data provision on the child's health state at his admission to school is being considered. The current change initiatives on the legislation in the field of preventive immunization are discussed.